2006
DOI: 10.1086/499816
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A Virus Infections in Travelers, 1988-2004

Abstract: The risk of hepatitis A virus infections has decreased by a factor of 10-50-fold over time, compared with findings from older studies. The risk, however, remains very considerable at many destinations, including frequently visited places, such as Mexico. Children of immigrants are a high-risk population. Strategies are needed to reach those at highest risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(37 citation statements)
references
References 25 publications
3
32
2
Order By: Relevance
“…Primary immunization can be achieved with one dose of HAV vaccine with a booster dose given 6 to 36 months later. 58,59 The immunological response to HAV vaccine in immunocompromised patients with cancer has not been systematically assessed. In a study including solid organ transplant recipients, G€ unther et al evaluated sero-conversion following 2 doses of the HAV vaccine in kidney and liver transplant recipients and found significant sero-conversion rates in 72% and 97% of patients respectively, versus 100% in healthy controls.…”
Section: Human Papillomavirus Vaccinementioning
confidence: 99%
See 2 more Smart Citations
“…Primary immunization can be achieved with one dose of HAV vaccine with a booster dose given 6 to 36 months later. 58,59 The immunological response to HAV vaccine in immunocompromised patients with cancer has not been systematically assessed. In a study including solid organ transplant recipients, G€ unther et al evaluated sero-conversion following 2 doses of the HAV vaccine in kidney and liver transplant recipients and found significant sero-conversion rates in 72% and 97% of patients respectively, versus 100% in healthy controls.…”
Section: Human Papillomavirus Vaccinementioning
confidence: 99%
“…62 In terms of Zoster vaccine (Zostavax, Merck, USA), this vaccine is recommended as a 1-time vaccination in individuals aged 60 years or older, and although it is clear that immunosuppression increases the risk of herpes zoster, there is a paucity of studies aimed at understanding the benefits and risks of administering this vaccine in this special population. 59 Tseng et al recently reported how older patients who receive the zoster vaccine were likely to continue to derive its benefits even if they become immunosuppressed; however, the study was not able to determine zoster vaccine safety or effectiveness in cancer patients who received zoster vaccine less than 60 days before beginning chemotherapy. 65,66 This study emphasizes the need to vaccinate immunocompetent patients older than 60 years of age, as currently no recommendations can be done about Zostavax vaccination in immunocompromised individuals.…”
Section: Live Attenuated Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Moreover, surveillance data on HAV infections in Switzerland during 1988-2004 were evaluated with a focus on international travelers with hepatitis detected after their return to Switzerland; and again children of immigrants were identified as a high-risk population. 18 The overall incidence of reported hepatitis A in travelers to countries of high or intermediate risk of transmission was 6.0-28.0 per 100 000 person-months abroad for travelers presumed to be non-immune. 18 Hepatitis A vaccination programmes for travelers are often ineffective, since many visitors to high-endemicity countries do not consult health professionals before departure.…”
mentioning
confidence: 98%
“…18 The overall incidence of reported hepatitis A in travelers to countries of high or intermediate risk of transmission was 6.0-28.0 per 100 000 person-months abroad for travelers presumed to be non-immune. 18 Hepatitis A vaccination programmes for travelers are often ineffective, since many visitors to high-endemicity countries do not consult health professionals before departure. 4 Healthcare workers who travel to a high endemicity country on repeated occasions will have a higher cumulative risk of hepatitis A.…”
mentioning
confidence: 98%